Strategies for Providing Marketing Staff in Islamic Banks - Tanjung, Hendri (Jurnal Manajemen, 2018)
Purpose of this paper is to find strategies for providing marketing staff in Islamic Banks. This paper contributes strategies aiming at the fulfillment of human resource of Islamic Banks in Indonesia and at the same time building curriculum for studying Islamic banking at undergraduate level. By using descriptive analysis on yearly statistical data of Islamic banks from 2005 to 2010, three figures obtained as estimation of the need of personnel in Islamic Banks at 2015. SWOT analysis is performed to identify strength, weakness, opportunity and threat of Islamic Banks. As a result, to recruit the estimated number of Islamic Banking staff, three ways could be employed, i.e. early recruitment program which requires improvement of curriculum at universities, recruiting from conventional banks with some training as addition, and building a new institution called “Institut Bankir Syariah Indonesia”.